Evaluasi Program Layanan Home Care Di Wilayah Kerja Puskesmas Batua Kota Makassar - Kasim, Nurwahidah; Palu, Basir; Ahri, Reza Aril (Window of Health : Jurnal Kesehatan, 2018)
Home Care program started in the Stone Clinic from may 2014 by the Government of the city of Makassar. He had to do in a program evaluation is a process whereby an orderly and systematic there is scope in the evaluation i.e. the input, process, and output. This research aims to know the evaluations program Home Care in clinics Stone Makassar City Year 2018. This research is a descriptive analysis with qualitative research to explore the phenomenon concerning the evaluation of the implementation of the Home Care program in health centers by using a method of Makassar Stone in-depth interviews (in-depth interviews) and observation. The results showed that the evaluation of the input stage, covering the 5. In terms of the Man in the Stone Clinic is the need to add a number of implementing power, especially for the Home Care program. In terms of the Machine, equipment used in the Home Care Service is complete. in terms of the Method were in accordance with the existing and standard operational procedure prevailing, in terms of Money the Ministry Home Care comes from a GRANT and that has been determined and was sent from the City Health Office of Makassar. For Materials (documentation/report) using a mobile phone camera and posted using WA to WA Group Ministry Home Care Clinics Stone, then the evaluation at this stage of the process needs to be proper coordination is not constrained in the implementation, and evaluation on the output stage, namely the lack of the skill of nurses to influence the independence of the patient